Spatial analysis of hiv cases in young adults and access to public services in a municipality of Paraná - Flaviane Marizete Limas; Marlise Lima Brandão; Daiane Siqueira de Luccas; Renato Cabral Bossle; Daiana Kloh Khalaf; Maria Marta Nolasco Chaves (O Mundo da Saúde, 2021)
This study aimed to analyze the spatial distribution of notified cases of HIV infection in young adults, from 2007 to 2016, and its relationship with accessibility to public health and social care services in a municipality in Paraná. This was an ecological study with georeferencing of notified HIV cases in young adults living in São José dos Pinhais, Paraná, from 2007 to 2016. The study analyzed data from the National System of Notifiable Diseases. A total of 309 cases of HIV/ AIDS infection were reported, and of these, 251 cases were georeferenced using the QGIS software. The geolocation of the cases was performed using the Google Earth Pro software. Concerning the characterization of the cases, there were 147 (47.5%) people with HIV and 162 (52.5%) with AIDS. Regarding gender, 97 (31%) were female and 212 (69%) were male. Meanwhile, the distribution of public centers were among the health sector (43) and the social assistance sector (16). Since the health facilities are located in the center of the urban space, and all social care facilities are within the urban area, these locations cannot guarantee accessibility to individuals who reside in more peripheral urban and rural areas. Therefore, there is a need for decentralization of services to ensure access to health promotion and disease prevention actions.